Konsep Kesetaraan Gender dalam Kisah Pengusiran Adam dan Hawa dari Surga: Sebuah Kajian Tematik Menggunakan Pendekatan Linguistik - Hamdi Putra Ahmad (Kafa`ah: Journal of Gender Studies, 2017)
There are not a few Muslims who make the story of Adam and Eve as an argument to consider women as a source of triggering sin. This study aims to find out the Qur'anic view of the story of the expulsion of Adam and Eve from heaven, expressingthe comprehensive view of the Qur'an about the chronology of the exorcism of Adamand Eve and outlining the causes of the expulsion of Adam and Eve from Heaven. This study uses thematic method with Q.S.  An-Nisa  (4): 1 and al-A'raf (7): 22 assources of data. Linguistic analysis was used to analyze the data. The results of thestudy showed that the emergence of this assumption is motivated by several reasons. Among the reasons is the history of Israiliyyat made by the classicalinterpreters as the primary source in interpreting the verses about Adam and Eve, which began at the end of the first century of Hhijriyah. The Israiliyyat narrations which speak of the story of Adam and Eve in general provide information which tends to make Eve a degrading party as well as a source of sin. This understanding ultimately affects the lowering of women's position over men in real life. In fact, if we examine directly the linguistic structure of the text of the verses in the Qur'an and read it holistically, and linked with the maqashid of equality of human creation, we will find that the Qur'an always makes Eve in an equal position with Adam.